Formulation and stability testing of gentamicin-Nigella sativa emulsions for osteo-healing application - Yusof, Fathin Athirah; Yaacob, Khairul Ikhwan; Mohd Yusof, Nazri; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi (2014)

(untitled)
An alternative osteo-healing formulation with osteo-healing properties was formulated by combining gentamicin and Nigella sativa (N. sativa) oil in an emulsion to reduce gentamicin toxicity effect over prolonged use in osteo-infection treatment. This work aims to test the aqueous solubility and physicochemical properties of the emulsion. Four emulsions (emulsion A, B, C and D) had been formulated, with final concentration of gentamicin was made constant at 0.1% (w/v) whereas N. sativa oil concentration was varied between 32.5% (v/v) to 46.4% (v/v) in all formulations. Then, stability studies of all emulsion were performed by centrifugation at (5000rpm, 5 minutes), at different storage conditions (8oC, 25oC and 50oC), organoleptic characteristics, freeze-thawcycle, pH determination, particle size measurement, zeta-potential analysis, and pH titration analysis. Results showed no phase separation after centrifugation for freshly prepared emulsions. Storage at 8oC, all emulsions also showed no phase separation at all-time points. At 25oC storage condition, three formulations were stable at day 7 but phase separation was formed in all emulsions by day 14showed good stability at day 7 and all emulsions formed phase separation at day 14. No emulsions were stable in storage temperature of 50oC. The particle size of the emulsions increased with an increment ofN. sativa oil concentration. Zeta-potential analysis showed a range of -32.2 ± 0.15 mV to -48.0 ± 0.45 mV. When pH titration analysis was performed, the zeta potential indicated that the emulsion stability was affected by acidic conditions. We concluded that the use of gentamicin-N. Sativaemulsions must take into account the storage condition with preference of low temperature and fresh preparation at higher alkalinity and the lowest possibility of N. sativa oil.